Regulatory roles of eugenol in paraquat-altered SNCA/LZTS3/MAPT in the cerebellum of Wistar rats - Obinna Onwe Uchewa; Augustine Oseloka Ibegbu; Samuel Okoronkwo Okafor; Joseph Alo Nwafor; Ogugua Augustine Egwu (Laboratory Animal Research)
Abstract Background The Microtubules-associated protein tau (MAPT), alpha-synuclein (SNCA), and leucine zipper tumor suppressor 3 (LZTS3) genes are implicated in neurodegeneration and tumor suppression, respectively. This study investigated the regulatory roles of eugenol on paraquat-altered genes. Results Forty male Wistar rats divided into five groups of eight rats were used. The control group received normal saline; the Paraquat (PQ)-untreated group received only Paraquat. The low dose of eugenol was 200 mg/kg, the medium dose of eugenol was 400 mg/kg, and the high dose of eugenol was 600 mg/kg. All groups except the control group received 10 mg/kg of PQ orally for 14 days at one-day intervals, allowing PQ in the rats for 28 days. Eugenol treatment started on the 29th and lasted 14 days. Motor impairments were determined using wire string and beam-walk; biomarkers were estimated using cerebellar homogenates, while frozen cerebellum was used to study LZTS3, MAPT, and SNCA gene expression. LZTS3 was significantly suppressed in the PQ-untreated group and highly expressed in the eugenol-treated group. The MAPT and SNCA genes were overexpressed in the PQ-untreated group compared to the control group. Eugenol significantly decreased the expression of these genes compared to that in the PQ-untreated group. Antioxidants were reduced considerably, and oxidative stress markers were increased significantly, which could have caused increased protein fibrillation and reduced limb functionality. Histology revealed that eugenol mitigated the alterations caused by Paraquat. Conclusions PQ can enhance tumor expression in addition to causing neurotoxicity, which decreases limb functionality, while eugenol, an antioxidant, can mitigate the effects of PQ.